Effect of the Reinforcement Phase on Indentation Resistance and Damage Characterization of Glass/Epoxy Laminates Using Acoustic Emission Monitoring - C. Suresh Kumar; K. Saravanakumar; P. Prathap; M. Prince; G. Bharathiraja; S. Kannan; S. Madhu; P. Kumaran (Advances in Materials Science and Engineering)
The effect of reinforcement phases on indentation resistance and damage behavior of glass/epoxy laminates was investigated in this research work. Woven glass fiber mat and nonwoven chopped glass fiber mat were used as fiber reinforcement phases for fabricating the laminates. Low-velocity impact and quasi-static indentation tests were performed on both laminates to investigate the contact behavior and energy-absorbing capability. Moreover, the acoustic emission (AE) technique was employed to monitor the indentation damage resistance. AE parameters including normalized cumulative counts (NCC), normalized cumulative energy (NCE), rise angle (RA), and felicity ratio (FR) were analyzed. The bidirectional laminates showed premature load drops and drastic changes in the normalized cumulative counts/energy profile in the beginning of loading cycles, indicating the development of macrodamage such as debonding/delamination. AE sentry function results of bidirectional laminates show longer PII function at the earlier stages, associated with minor PIII function and greater PIV function, indicating the continuous degradation and progression of damage. In contrast, the chopped laminates exhibited superior postimpact performance than the bidirectional laminates. The presence of randomly oriented fibres prevents the delamination crack propagation during compression loading, which was attributed with the increased residual compressive strength.